THE EFFECTIVENESS OF THE USE OF JOSAMYCIN IN THE TREATMENT OF URETHROGENIC PROSTATITIS ASSOCIATED WITH CHLAMYDIA INFECTION - Islamov Nurali Hikmatovich; Ibragimova Elnara Farmanovna; Yermanov Rustam Temirovich; Mamirov Vasliddin Amirovich; Abdullaev Xasan Davlatovich (International Engineering Journal For Research & Development, 2021)
Treatment of urogenital chlamydia remains a difficult practical task. Due to the formation of resistance of these microorganisms to antibiotics, the duration of therapy increases, relapses often occur. At the same time, the increase in the frequency of this pathology currently tends to increase and is observed mainly among young and middle-aged people, which leads to a decrease in not only copulatory, but also reproductive function.In this regard, the choice of an effective drug in the treatment of prostatitis associated with chlamydia infection still remains an urgent problem.